THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE , MEDIATED BY JOB SATISFACTION AT PT. MONRAD INTAN BARAKAT - Budiyannur, Budiyannur; Ibnu Al Saudi (INFOKUM, 2021)
The purpose of this study was to determine and analyze the effect of individual characteristics and organizational culture on performance mediated by job satisfaction at PT Monrad Intan Barakat, Banjar Regency. The respondents of this research were 58 employees of PT Monrad Intan Barakat Banjar Regency, with probability sampling technique or random. The analysis tool used the SmartPLS version 3.0 application. The results of the study found that (1) individual characteristics affect job satisfaction, (2) organizational culture affects job satisfaction, (3) individual characteristics do not affect performance, 4) organizational culture does not affect performance, and (5) job satisfaction has an effect on performance. performance. Meanwhile (6) Job Satisfaction mediates the effect of Individual Characteristics on Performance and (7) Job Satisfaction mediates the influence of Organizational Culture on Performance